Attentional capture: Role of top-down focused spatial attention and the need to search among multiple locations. Issue 1 (16th March 2017) - Bertleff, S.; Fink, G. R.; Weidner, R.
ABSTRACT: Top-down focused spatial attention can counteract bottom-up attentional capture of an irrelevant but salient distractor outside the attentional focus. The present behavioural study differentiates two alternative concepts accounting for the absence of attentional capture under top-down focused attention. In particular, top-down focused attention may counteract attentional capture by altering salience coding outside the focus of attention. Alternatively, spatially focusing on a pre-defined region of potential target locations may omit the need to search among multiple salience signals, thereby eliminating the tendency of unattended stimuli to compete for attentional selection and, hence, to capture attention. Spatial cues explicitly indicating a variable number of potential target locations preceded the additional singleton paradigm to gradually manipulate the need to search for a target (i.e., to select a target from an array of distractors) and to determine its effects on attentional capture. Attentional capture occurred only when a salient distractor was located at potential target locations and never occurred when located outside the attended spotlight. This finding was independent of the parametrical variations related to the need to search for the target, which did not modulate attentional capture either. Accordingly, our data suggest that the presence or absence of salience-based distraction of unattended stimuli is not per se affected by the need to select a target from multiple salience signals.